The undisclosed renminbi basket: are the markets telling us something about where the renminbi - US dollar exchange rate is going? - Michael Funke; Marc Gronwald (Center for Economic Studies and ifo Institute (CESifo), 2008)
On 21 July 2005 China adopted an undisclosed basket exchange rate regime. We formally assess and envisage the gradual evolution of the renminbi over time. We utilize nonlinear dependencies in the renminbi exchange rate and describe the smooth transition of the renminbi/U.S. dollar (RMB/USD) exchange rate using the family of time-varying autoregressive (TV-AR) models. Specifically, the nonlinear models allow for a smooth transition from one optimal level to another. Our estimation results imply that the RMB/USD exchange rate will likely be about 7.10 RMB/USD in summer/autumn 2009.
Keywords: C22; F31; F37; 330; China; renminbi; de facto exchange rate regime; TV-AR model; TV-AR-GARCH model; Wechselkurs; Wechselkurssystem; Währungskorb; Autokorrelation; ARCH-Modell; China; USA